Relationality in Organizational Research: ExploringThe Space Between - Bradbury, Hilary; Lichtenstein, Benyamin M. Bergmann (Organization Science, 2000)
Relationships and interactions should be an important focus of attention in organizational scholarship. In contrast to traditional research approaches that focus on independent, discrete entities, methodologies oriented to relational concerns in organizations allow researchers to study the intersubjective and interdependent nature of organizational life. In addition to providing historical and philosophical bases for a perspective which emphasizes relationality, we review the growing number of methods that capture relational aspects of organizational life. Examples include network analysis, and “complexity” modeling, correspondence analysis and participatory research, case study methods, the learning history approach, psychometrics, and action inquiry. Our goal is to establish a “palette” of methodological choices for the researcher interested in operationalizing a relational perspective within organizational research/practice.